Hematological Characteristics and Erythrokinetic Indices in Little Ground Squirrels During Arousal from Hibernation - Shihamirova, Zainab; Dzhafarova, Albina; Klichkhanov, Nisred (Problems of Cryobiology and Cryomedicine, 2020)
During hibernation, the small mammals pass through multiple cold (torpor) and warm (arousal) phases, as well as adaptive changes in red blood cells are vital for an adequate oxygen supply to tissues. Here, we have analyzed the structural and functional indices of red blood cells in little ground squirrels during arousal from hibernation. In a torpid state, a count of red blood cells, HGB and MCH levels in blood were established as not significantly changed, but MCV and HCT decreased, while MCHC and RDW increased as compared to the control. In hibernating animals, the reticulocyte count in blood decreased and the period of erythrocyte elimination in bloodstream was shortened, but the ability to produce the red blood cells remained at the control level. During arousal, the body temperature of 25-30°C was critical for rearrangement of structural and functional parameters of red blood cells. This was evidenced by RDW increase and the tendency to rise in HCT, MCV; high reticulocyte count in blood and extended time of their maturation; increased half-life of red blood cells. When the body temperature was fully normalized, the production of red blood cells was significantly increased due to the reduced reticulocyte maturation time. Probl Cryobiol Cryomed 2020; 30(2): 132–147